Agroforestry. Proceedings of a seminar held in CATIE, Turrialba, Costa Rica, 23 February - 3 March, 1981 - Heuveldop, Jochen (CATIE, Turrialba (Costa Rica) German Foundation for Technical Cooperation, San José (Costa Rica) German Foundation for International Development, San José (Costa Rica), 2014)
Trad. del Alemán: Fachseminar "Agroforstwirtschaft" Bericht - August 1981